2004
DOI: 10.1080/15389580490435097
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Pedestrian Trauma Study: A Pilot Project

Abstract: The WalkSafe program was shown to improve the pedestrian safety knowledge of elementary school children. Future research will include implementing the WalkSafe program at each elementary school within a single high-risk district.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Valid data were not collected partly because the sample of walkers was small and the quality of the recorded videos was poor. 53,54 Similar to other investigators, we found education to be an effective strategy for teaching injury prevention. 55 In the pilot study, we were able to begin to demonstrate that the educational street-crossing lessons that children learned in school could be translated into correct street-crossing behavior shortly after implementation of the program.…”
Section: The Walksafe Programsupporting
confidence: 89%
See 1 more Smart Citation
“…Valid data were not collected partly because the sample of walkers was small and the quality of the recorded videos was poor. 53,54 Similar to other investigators, we found education to be an effective strategy for teaching injury prevention. 55 In the pilot study, we were able to begin to demonstrate that the educational street-crossing lessons that children learned in school could be translated into correct street-crossing behavior shortly after implementation of the program.…”
Section: The Walksafe Programsupporting
confidence: 89%
“…55 In the pilot study, we were able to begin to demonstrate that the educational street-crossing lessons that children learned in school could be translated into correct street-crossing behavior shortly after implementation of the program. 53,54 This study has now been expanded and revised and the behavioral component will be investigated again this year by also identifying the grade of the child. The WalkSafe program has been successful in significantly lowering the number of childhood pedestrian injuries (Table 4).…”
Section: The Walksafe Programmentioning
confidence: 99%
“…As demonstrated in our pilot program (Phase III), child education programs are the most effective approach to prevention (Hotz et al, 2004;Schleber & Vegega, 2001). There is a wide acceptance of the value and necessity of teaching pedestrian safety skills by using knowledge-based approaches and practical training exercises in a real traffic environment (Zeedyk et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…A school-based educational injury prevention program, the WalkSafe program (Hotz et al, 2004), was implemented targeting students from kindergarten through grade five (standardized for each grade level). This comprehensive, pedestrian safety program originated from a pilot study for pediatric pedestrian trauma (PPT).…”
Section: Educational Interventionmentioning
confidence: 99%
See 1 more Smart Citation